How Crowdfunding Shapes Venture, Product and Market Decisions: A Multiple Case Study of Philippine-based Microenterprises - Vergara, Raymond Allan G. (Future Science / FSH-PH Publications, 2026)
Microenterprises face constraints in accessing capital, markets, and entrepreneurial support systems, which limit their capacity for venture creation and growth. Crowdfunding emerged as an alternative mechanism with the potential to address these challenges; yet its role in shaping venture creation decisions remains underexplored in emerging economies. Using an exploratory, qualitative, multiple-case approach, this study examines how crowdfunding influences the venture-creation and decision-making processes of Philippine-based microentrepreneurs. Drawing on eight cases of successfully crowdfunded enterprises, the study investigates entrepreneurs’ motivations for participating in crowdfunding, their experiences before, during, and after campaigns, and the critical transition points that shape venture outcomes. Findings demonstrate that crowdfunding is a market-validation tool rather than a financial tool. While funding initially motivates participation, crowdfunding’s most significant benefits are non-financial: market and consumer insight, product feedback, brand visibility, and access to broader networks. More importantly, these resources inform decisions to launch new ventures, develop new products, enter new markets, or pivot strategically, enabling low-risk market experimentation prior to full venture commitment. Building on these findings, the study refines crowdfunding entrepreneurial frameworks by extending commitment beyond new venture creation to include product- and market-level decisions, and contributes an alternative venture creation pathway for resource-constrained microenterprises.